The management of teachers’ personality competence to enhance discipline among elementary school students - Ani Susilawati; Sobari (At Turots: Jurnal Pendidikan Islam, 2025)
The discipline of elementary school students is a crucial foundation for character development and the achievement of national education goals. Teachers play a strategic role as role models in instilling discipline values through personality competencies reflected in integrity, exemplary behavior, consistency, and the ability to nurture student behavior. Implementing these competencies requires planned management through the functions of planning, organizing, implementing, and supervising. This study employed a qualitative approach with a case study method at SDN Sukawangi 2 Warungkondang and SDN Kembangmanis 2 Cugenang, Cianjur Regency. Data were collected through in-depth interviews, classroom observations, and document analysis, validated by triangulation of sources, techniques, and time, and analyzed using an interactive model comprising data reduction, data presentation, and conclusion drawing. The results indicate that teacher personality competency management is implemented through four management functions: (1) Planning, emphasizing exemplary behavior, integrity, and consistency supported by internal policies, reflective forums, and continuous training; (2) Organizing, which strengthens teacher competencies through role-model assignments, coordination of habituation activities, and provision of coaching tools; (3) Implementation, where teachers act as role models, motivators, and consistent enforcers of rules; and (4) Supervision, involving monitoring student discipline, evaluating teacher personality, and following up with peer mentoring, reflection forums, and individual guidance. The findings align with educational management theories (Mulyasa, Terry, Sergiovanni) and government policies on teacher competencies. Challenges include differences in discipline among teachers, limited coordination time, student resistance to humanistic approaches, and limited school resources. The success of discipline development strongly depends on synergy between organizational structure, school culture, and adequate coaching instruments.